Menelaah kondisi kesejahteraan masyarakat desa Arjosari melalui pendekatan observatif dalam kegiatan kuliah kerja mahasiswa - Wildani, Muhammad Baihaqi Rahmat; Zulfa, Anis Azkiyah; Ramadani, Kirana; Nirmala, Shely Sindi; Pratiwi, Putri Ayu; Wafiroh, Nahdhiyah Tazkiyatul; Putri, Dwi Andina; Humairoh, Nur; Amiruddin, Muhammad (Maliki Interdisciplinary Journal, 2026)
Community welfare serves as a fundamental indicator of successful rural development, reflecting the quality of social, economic, educational, and environmental conditions within a society. This study aims to examine the welfare conditions of the residents of Arjosari Village through an observational approach implemented as part of a Community Service Program (Kuliah Kerja Mahasiswa/KKM). Employing a qualitative research design, data were collected through direct field observations, community engagement, and systematic documentation of socio-economic and environmental conditions. The collected data were analyzed descriptively to provide a factual and contextual understanding of community welfare. The findings reveal that the welfare status of Arjosari Village residents varies considerably, as evidenced by disparities in access to educational services, healthcare facilities, household economic conditions, and the quality of the residential environment. These findings indicate that rural development efforts continue to face challenges in ensuring equitable access to and quality of essential public services. This study offers valuable baseline information that can serve as an evaluative resource and a policy reference for designing more inclusive, sustainable, and community-centered rural development programs aimed at enhancing public welfare.